Alcinous’ Garden – Archetypical, Paradigmatic or Simply Imagined? - Michał Bzinkowski
In this article, I offer a new reading of the well-known passus from Homer’s Odyssey containing a description of the so-called ‘garden of Alcinous’ (Od. 7, 112–132). In the first instance, I draw attention to a context in the Homeric epic, given the formulaic language of the epic and the ambiguity of reading certain terms. In the following section, I focus on the presence of this passus in works of selected Byzantine authors, attempting to answer the question for what purpose they used this very reference. Finally, I try to show the reception of the aforementioned motif in modern times, namely in 18th century Britain, where it appears as a reflection of a lost ideal that needs to be recreated and adapted to new times. All of this serves, on the one hand, to refute the commonly held opinions repeated by historians of gardening that the first model of gardens could be found as early as Homer. Secondly, my findings also cast doubt on the question of the garden of Alcinous as a model for Byzantine literary gardens. Thirdly, they show to what extent the bearing of certain ideas can be misrepresented in translation and what consequences this issue has.